A New Record of the Snapping Shrimp Alpheus lobidens from the Iraqi coast (Malacostraca, Decapoda, Alpheidae) : Alpheus lobidens De Haan, 1849 from the Iraqi coast - Yasser, A. Gh.; Naser, M. D. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2023)
Based on newly collected material from the Iraqi coast, the status of the common intertidal snapping shrimp, Alpheus lobidens De Haan, 1849 species complex, is dis[1]cussed. Based on several morphological characteristics as well as the color pattern, the material examined herein strongly supports the validity of A. lobidens.